Proceedings of the 3rd Clinical Natural Language Processing Workshop 2020
DOI: 10.18653/v1/2020.clinicalnlp-1.6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Transfer Learning for Adverse Drug Event (ADE) and Medication Entity Extraction

Abstract: We evaluate several biomedical contextual embeddings (based on BERT, ELMo, and Flair) for the detection of medication entities such as Drugs and Adverse Drug Events (ADE) from Electronic Health Records (EHR) using the 2018 ADE and Medication Extraction (Track 2) n2c2 data-set. We identify best practices for transfer learning, such as languagemodel fine-tuning and scalar mix. Our transfer learning models achieve strong performance in the overall task (F1=92.91%) as well as in ADE identification (F1=53.08%). F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The introduction of SpanBERT [9] architecture to ADE extraction task outperformed competing models [10] on Social Media Mining for Health (SMM4H) and CSIRO Adverse Drug Event Corpus (CADEC). [11,12] Narayanan et al [13] evaluated various biomedical contextual embeddings and models using the 2018 National NLP Clinical Challenges (n2c2) shared task Track 2 data on ADEs and Medication Extraction, [14] demonstrating the importance of BERT structure. In recent work on adverse event (AE) detection, Chopard et al [15] confirmed the feasibility of automating coding of AEs described in the narrative section of serious AE report forms.…”
Section: Background and Significancementioning
confidence: 99%
“…The introduction of SpanBERT [9] architecture to ADE extraction task outperformed competing models [10] on Social Media Mining for Health (SMM4H) and CSIRO Adverse Drug Event Corpus (CADEC). [11,12] Narayanan et al [13] evaluated various biomedical contextual embeddings and models using the 2018 National NLP Clinical Challenges (n2c2) shared task Track 2 data on ADEs and Medication Extraction, [14] demonstrating the importance of BERT structure. In recent work on adverse event (AE) detection, Chopard et al [15] confirmed the feasibility of automating coding of AEs described in the narrative section of serious AE report forms.…”
Section: Background and Significancementioning
confidence: 99%
“…In a similar vein, Peng et al [16] have proposed a benchmark setting (called BLUE) to evaluate pre-trained model in a clinical setting, showing that BERT model pre-trained on PubMed abstracts and MIMIC-III was superior (we refer to it as BlueBert in the rest of the paper). Recently, biomedical contextual embeddings have also been applied to improve the performance of adverse drug identification and the medication extraction task [9], [17].…”
Section: Related Workmentioning
confidence: 99%
“…Transfer learning can be effective for medication extraction from clinical texts [ 8]. In this paper, we address how named entity recognition and relation extraction can be performed for medication-related incident reports, even when few gold-standard data are available [4].…”
Section: Introductionmentioning
confidence: 99%